2022
DOI: 10.1007/s10278-022-00609-8
|View full text |Cite|
|
Sign up to set email alerts
|

A Dedicated Tool for Presurgical Mapping of Brain Tumors and Mixed-Reality Navigation During Neurosurgery

Abstract: Brain tumor surgery requires a delicate tradeoff between complete removal of neoplastic tissue while minimizing loss of brain function. Functional magnetic resonance imaging (fMRI) and diffusion tensor imaging (DTI) have emerged as valuable tools for non-invasive assessment of human brain function and are now used to determine brain regions that should be spared to prevent functional impairment after surgery. However, image analysis requires different software packages, mainly developed for research purposes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 19 publications
(21 reference statements)
0
12
0
Order By: Relevance
“…In 30 studies (38%), the use of a head-mounted device for neurosurgery was evaluated ( Supplemental Digital Content 2, Table 1 , http://links.lww.com/ONS/B48). 10-86 In most of these studies, the HoloLens (Microsoft) was used for AR visualization. In 26 studies (32%), an image overlay, for either the microscopic or endoscopic field of view, was used.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 30 studies (38%), the use of a head-mounted device for neurosurgery was evaluated ( Supplemental Digital Content 2, Table 1 , http://links.lww.com/ONS/B48). 10-86 In most of these studies, the HoloLens (Microsoft) was used for AR visualization. In 26 studies (32%), an image overlay, for either the microscopic or endoscopic field of view, was used.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies reported on multiple evaluation metrics ( Supplemental Digital Content 3, Table 2 , http://links.lww.com/ONS/B49). 10-83,85-90 Based on the results of this review, the following evaluation categories have been defined: (1) registration accuracy, (2) clinical outcome, (3) time measurements, (4) task performance, (5) technical reliability, and (6) user perception (Table).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The former (i.e., VR) is able to immerse the users in a fully artificial digital environment, while the latter (i.e., AR) has the capability to overlay virtual objects in the real-world environment. In the AR approach, virtual information is "anchored" to the real object, and this combination is visualized via a head-mounted display (HMD) [9]. Here, the HoloLens (HoloLens; Microsoft Corporation, Redmond, Washington) is one such example that has been shown to be useful in the surgical innovations [7,10].…”
Section: Introductionmentioning
confidence: 99%
“…Although MR systems have been used as a teaching tool for simulation in adult neurosurgery, their use in children is comparatively unexplored [15]. Furthermore, our literature search reveals that most of the publications on neurosurgical MR applications stem from Europe and North America [9,16,17]. Overall, similar systems for pediatric neurosurgery from our part of the world in Southeast Asia remain underrepresented at this point in time.…”
Section: Introductionmentioning
confidence: 99%